Investigation of the mechanism of chenodeoxycholic acid in treating acute lung injury through network pharmacology and experimental validation - He, Chong; Jiang, Mengmeng; Xiong, Qian; Huang, Zuoxi (Scientific reports, 2025)
Network pharmacology and molecular simulation techniques were employed to predict the potential targets and signaling pathways of chenodeoxycholic acid in the treatment of acute lung injury. Subsequently, its therapeutic effects on acute lung injury were preliminarily validated using animal experiments. The target of Chenodeoxycholic acid in the treatment of acute lung injury was predicted using network pharmacology. Key active ingredients and core targets were further validated using molecular docking studies. Lipopolysaccharide was used to establish a mouse model of acute lung injury to study the effect of chenodeoxycholic acid on acute lung injury. A total of 73 potential targets of Chenodeoxycholic acid for the treatment of acute lung injury were identified, primarily HSP90AA1, STAT3, HSP90AB1, EP300, and NFKB1. These core targets influence pathways associated with bile secretion, prostate cancer, and receptor activation in chemical carcinogenesis. These targets modulate various processes, including steroid metabolism, steroid biosynthesis, and intracellular receptor signaling pathways, thus contributing to the treatment of acute lung injury. Molecular docking results indicated that Chenodeoxycholic acid exhibited strong binding affinity for the core targets, with docking energies ranging from −5.6729 to −7.4138 kcal/mol. The reliability of the results was further verified by molecular dynamics simulations. Results from animal experiments demonstrated that Chenodeoxycholic acid effectively ameliorated pathological injury to lung tissue in mice with acute lung injury, decreased levels of IL-6 and TNF-α (P < 0.01), and increased levels of IL-10 (P < 0.01). The mRNA expression levels of EP300, HSP90AB1, MTOR, and STAT3 were inhibited, while the mRNA expression level of NR1H4 was significantly increased (P < 0.01). Chenodeoxycholic acid can effectively improve acute lung injury.